ASSESSING THE IMPACT OF MALNUTRITION ON CHILD MORTALITY RATES IN SOMALIA - Nirmala. M. (CV. Fahr Publishing, 2024)
Malnutrition is a significant public health challenge in Somalia, contributing to high child mortality rates and long-term developmental issues. This study assesses the impact of malnutrition on child mortality in Somalia, focusing on the key factors contributing to malnutrition and the effectiveness of existing interventions. A mixed-methods approach was used, combining quantitative surveys and qualitative interviews. The quantitative component involved structured surveys with 400 respondents, including caregivers and healthcare providers, to gather data on stunting, wasting, and food insecurity. The qualitative aspect consisted of semi-structured interviews and focus group discussions with caregivers, healthcare workers, and community leaders to explore socio-economic and logistical barriers to malnutrition interventions. The results showed that 45% of children in rural areas were stunted, compared to 30% in urban areas. Micronutrient deficiencies were prevalent, particularly in rural and refugee camp regions. Community-based nutrition programs proved to be the most effective, with success rates of 75% in rural areas, compared to food aid (40%) and micronutrient supplementation (55%). The findings underscore the importance of community-driven approaches to combating malnutrition in Somalia. Sustainable solutions should focus on local food production, nutrition education, and improving healthcare access. This study contributes to the global understanding of malnutrition in conflict-affected regions, providing valuable insights for policy and intervention design.